Edukasi manajemen stress pada remaja dengan relaksasi nafas dalam dan relaksasi otot progresif - Triyoso, Triyoso; Furqoni, Prima Dian; Rilyani, Rilyani; Wandini, Riska (JOURNAL OF Public Health Concerns, 2024)
Background: Adolescence is the most important period in human life, and adolescence refers to the stage of life that represents the transition from childhood to adulthood. Stress in the younger generation throughout the world occurs in both developed and developing countries. The prevalence of stress and anxiety in adolescents worldwide ranges from 5 to 70%. In the United States alone, 60% of suicide victims suffer from stress and depression. In addition, the prevalence of stress among Korean teenagers was found to be 39.3% in 2019. In Indonesia the prevalence of stress among teenagers increase from year to year, reaching 6.0% of the population. Purpose: Increasing teenagers' knowledge about proper stress management through deep breathing relaxation techniques and progressive muscle relaxation techniques. Method: The community service method carried out is using the socialization method, and filling out questionnaires for Permata Bunda IT High School students. Results: There were 16 participants (100%) who were able to carry out deep breathing relaxation and there were 16 participants (100%) who were able to carry out progressive muscle relaxation. Conclusion: The breathing relaxation technique achieved an incredible 100% success rate among 16 participants, highlighting its undeniable effectiveness in reducing stress. Likewise, Progressive Muscle Relaxation exhibits universal adaptability with a 100% success rate, positioning it as a powerful technique in combating the stressors of modern life. Keywords: Relaxation Techniques; Stress Management; Teenagers. Pendahuluan: Masa remaja merupakan masa terpenting dalam kehidupan manusia, dan masa remaja mengacu pada tahap kehidupan yang mewakili peralihan dari masa kanak-kanak menuju masa dewasa. Stres pada generasi muda di seluruh dunia terjadi baik di negara maju maupun  berkembang. Prevalensi stres dan kecemasan pada remaja di seluruh dunia berkisar antara 5 hingga 70%. Di Amerika Serikat saja, 60% korban bunuh diri menderita stres dan depresi. Selain itu, prevalensi stres di kalangan remaja  Korea ditemukan sebesar 39,3% pada tahun 2019. Di Indonesia prevalensi stres di kalangan remaja meningkat dari tahun ke tahun,  mencapai 6,0% dari populasi. Tujuan: Meningkatkan pengetahuan remaja mengenai manajemen stres yang baner melalui teknik relaksasi nafas dalam dan teknik relaksasi otot progresif. Metode: Metode pengabdian masyarakat yang dilakukan yaitu menggunakan metode sosialisasi, dan pengisian kuesioner kepada siswa SMA IT Permata Bunda. Hasil: Terdapat 16 partisipan (100%) mampu melakukan relaksasi pernapasan dalam dan terdapat 16 partisipan (100%) yang mampu melakukan relaksasi otot progresif. Simpulan: Teknik relaksasi pernapasan mencapai tingkat keberhasilan 100% yang luar biasa di antara 16 partisipan, menyoroti efektivitasnya yang tidak dapat disangkal dalam mengurangi stres. Demikian pula, Relaksasi Otot Progresif menunjukkan kemampuan beradaptasi universal dengan tingkat keberhasilan 100%, memposisikannya sebagai teknik yang kuat dalam melawan pemicu stres dalam kehidupan modern.